Serum Immunoglobulin G Levels in Small-for-Dates Newborn Babies. Issue 242 (August 1970) - Papadatos, C.; Papaevangelou, G. J.; Alexiou, D.; Mendris, J.
Abstract : Immunoglobulin G levels have been studied in 47 small-for-dates (SFD) and 197 singleton babies of normal birthweight for their gestational age. The IgG values in the SFD babies were below those expected for the normal newborn of an equivalent gestational age, but above those of the normally growing baby of equivalent birthweight. There is a statistically significant difference in the slopes of the regression lines in the two groups whether IgG is plotted against birthweight or gestational age.